Playing with the Past - Champion, Erik.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
How can we increase awareness and understanding of other cultures using interactive digital visualizations of past civilizations? In order to answer the above question, this book first examines the needs and requirements of virtual travelers and virtual tourists. Is there a market for virtual travel? Erik Champion examines the overall success of current virtual environments, especially the phenomenon of computer gaming. Why are computer games and simulations so much more successful than other types of virtual environments? Arguments that virtual environments are impeded by technological constraints or by a paucity of evaluation studies can only be partially correct, for computer games and simulations are also virtual environments. Many of the underlying issues are caused by a lack of engagement with the philosophical underpinnings of culture, presence and inhabitation, and there are few exemplars that engage the public with history and heritage using interactive media in a meaningful and relevant manner. The intention of Playing With the Past is to help designers and critics understand the issues involved in creating virtual environments that promote and disseminate historical learning and cultural heritage through a close study of the interactive design principles at work behind both real and virtual places. Topics discussed include the design of virtual environments, and especially virtual heritage environments, virtual place-making, cultural presence, the pros and cons of game-style interaction, augmented reality projects, and appropriate evaluation methods. Virtual heritage environments discussed in the book include projects from Antarctica, Australia, Mexico, Malta, Egypt, Babylon, the Netherlands, Cambodia, and India.
1. Introducing Virtual Travel -- 2. Virtual Environments -- 3.Virtual Places -- 4. Cultural and Social Presence -- 5. Game-Style Interaction -- 6. Playing With The Past -- 7. Augmenting the Present With the Past -- 8. Evaluating Virtual Heritage -- 9. Conclusion -- Index.
Keywords: Computer science; Multimedia systems; Social sciences -- Data processing; Information systems; Computer aided design; Computer Science; Computer Appl. in Social and Behavioral Sciences; Computer Appl. in Arts and Humanities; Media Design; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Computer-Aided Engineering (CAD, CAE) and Design